2008
DOI: 10.1016/j.ijgo.2007.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of prognosis in patients with peripartum cardiomyopathy

Abstract: Cut-off values for initial left ventricular ejection fraction of >27% and left ventricular end-systolic diameter of < or =5.5 cm may predict recovery of left ventricle function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 17 publications
3
63
1
Order By: Relevance
“…For example, at the end of six months of follow up, LVEF in the South African patients had increased to between 42.1 and 44.1%,6,7,11,20 compared to 44.9% in the Zimbabwean patients. However NYHA functional class at baseline has been shown to more consistently predict mortality in patients with PPCM 6,7,25. The baseline NYHA functional class of patients in the Zimbabwean cohort was lower than that in South African studies.…”
Section: Discussionmentioning
confidence: 76%
“…For example, at the end of six months of follow up, LVEF in the South African patients had increased to between 42.1 and 44.1%,6,7,11,20 compared to 44.9% in the Zimbabwean patients. However NYHA functional class at baseline has been shown to more consistently predict mortality in patients with PPCM 6,7,25. The baseline NYHA functional class of patients in the Zimbabwean cohort was lower than that in South African studies.…”
Section: Discussionmentioning
confidence: 76%
“…First the great majority of the studies have been performed in single centers, with small numbers of patients, using different definitions of improvement in LV ejection fraction ranging from improvements in ejection fraction of 5% to 15% [4,5], although the great majority of studies have used 10%. Second, the definition for recovery of LV function has ranged from ejection fractions of greater than 40% to 50% [6]. For the purpose of this review, we will use the cut-off of 50% as a measure of complete LV recovery since this has been used by the majority of studies.…”
Section: Natural History Of LV Recoverymentioning
confidence: 99%
“…At the time of diagnosis, if LVEF is larger than 27% or LVESD is 5.5 cm or lower, it is reported that there is an increased possibility of recovering left ventricle function [6]. In our case, the LVEF of the patient was 39% and LVESD was 4.3 cm at the initial diagnosis, so left ventricle function was expected to return to normal.…”
Section: Discussionmentioning
confidence: 67%